Afterlives of ancient rock-cut monuments in the Near East: carvings in and out of time - Ben-Dov, Yonatan; Rojas, Felipe (Culture and history of the ancient Near East, 2021)
Intro -- Contents -- Preface -- Figures and Tables -- Notes on Contributors -- Chapter 1 Introduction -- Chapter 2 Entangled Images: Royal Memory, Posthumous Presence, and the Afterlives of Assyrian Rock Reliefs -- Chapter 3 Narrating Temporality: Three Short Stories about Egyptian Royal Living-rock Stelae -- Chapter 4 Forgetting an Empire, Creating a New Order: Trajectories of Rock-cut Monuments from Hittite into Post-Hittite Anatolia, and the Afterlife of the "Throne" of Kızıldağ -- Chapter 5 A Carving in Antioch: History, Magic, Antiquarianism, Archaeology -- Chapter 6 Herodotus and Empire: Ancient Near Eastern Monuments and Their Cultural Recycling in Herodotus' Histories -- Chapter 7 Sculpting in Time: Rock Reliefs, Inscriptions and the Transformation of Iranian Memory and Identity -- Chapter 8 Éminences grises: Emergent Antiquities in Seventeenth-Century Iran -- Chapter 9 Neo-Babylonian Rock Reliefs and the Jewish Literary Imagination -- Chapter 10 Translatio studii: Stelae Traditions in Second Temple Judaism and Their Legacy in Byzantium -- Chapter 11 The Long History of an Imaginary Inscription: Josephus' Two Pillars in Early Modern European Histories of Astronomy -- Name Index -- Subject Index -- Ancient Sources Index.